Expanding the Limitations of the Protection and Processing of Children’s Personal Data: An Overview of Current Regulations, Challenges, and Recommendations - Sihabudin, Sihabudin (Faculty of Law, Universitas Brawijaya, 2023)
Protection of personal data in the digital era is increasingly becoming a challenge, especially in protecting children's data. Children who easily access social media and do not fully understand the dangers of spreading personal data will become easy targets for criminals. Moreover, now parents also often either intentionally or unintentionally share children's data on social media. This study evaluates the urgency of implementing specific protection for children’s personal data and identifies the limitations of the current regulations regarding the protection and processing of these data. Additionally, we highlight the inadequacy of protection for children’s personal data in Indonesia’s laws. This study proposes an expanded limitation to protect and process children’s personal data. The legal method in this study adopts a descriptive analytical approach using normative doctrinal methods and employs statute and comparative approaches with General Data Protection Regulation and Children’s Online Privacy Protection Act of 1998 in order to address the issue regarding personal data protection for children. The study concludes with a recommendation to amend the Personal Data Protection Law No. 27/2002 and promotes the protection for children’s data privacy.